MEMBANGUN DAYA SAING UKM DALAM PEREKONOMIAN NASIONAL - Darwanto, Bapak (STIE Totalwin Semarang, 2011)
Small-Medium Enterprise (SME) has important role in national economy on job creating and output. SME create job more than big industry. Eventhough SME role on share of national income is less than big industry. This situation is caused by weakness of competitiveness and productivity of small-medium enterprise. Empowering of competitiveness and productivity is important to overcome this problem. Increasing productivity and competitiveness program on new sector that has high local resource and base on technology would be solution to empowering competitiveness of SME